ปัจจัยที่มีผลต่อการยอมรับบทบาททางการเมืองของผู้นำสตรีท้องถิ่น : ศึกษากรณีกำนันผู้ใหญ่บ้านที่เป็นสตรียอดเยี่ยมประจำปี 2540 - รวิวรรณ วรรณพานิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This is the study of factors contributing to how the constituents accept a woman as the community leader. The study made use of the case that some women were elected as "The Awarded Female Sub-District and Village Headmen of 1997". The questionnaire technique was used as the research instrument. The questionnaires were answered by 198 people who were work colleagues of The Awarded Female Commune and Village Headmen through random sampling method The questionnaires were aimed at investigating 3 related areas namely ‘personal quality’, ‘professional knowledge’ and ‘personal quality’. ‘Personal quality’ included modesty, gentle, ethic, financial contribution request, patience, farness and dedication. Regarding ‘professional knowledge’, it included missions on culture and tradition, career promotion, community development, law enforcement, fact finding, trouble shooting, and community facility provision. Regarding ‘personal ability’, it included having vision, competence and resourcefulness holding effective meetings, charisma, coordination, face-to-lace meeting with people good planning. good decision making. generosity, monitoring and following up work, as well as enthusiasm. The result of the study were: 1 The people mostly accept the ‘personal ability as good organizers’ of the female local leaders, and consider the ‘personal quality: financial contribution request’ at the lower level. 2 The people s acceptance of female local leaders a resulted from ‘personal ability’ not their competence in job description as fixed by the laws concerned.